Bruno Rombi’s Environmental Poetry Sardinia, an Island and a Metaphor (Revue de l'Institut des Belles Lettres Arabes, 2012)
Bruno Rombi, a known and acknowledged contemporary Italian poet, is deeply inspired by his natural environment (especially of Sardinia where he’s born) and a sensitive interpreter of life gradually discovered through observation, reflection and assimilation. His ecological poetry is a celebration of the empirical beauty of Nature and an authentic effort to come to terms with the mystery of life and its universal beauty. His remarkable contribution to poetry, both Italian and Mediterranean, transcends the mere description and becomes an interpretation of existence itself, evolving on two parallel layers, literal and figurative. The world of the sense he explores becomes in itself insufficient to provide the meaningfulness post-modern man is deeply looking for.